An investigation of the microbiology and biochemical properties leading to extended shelf-life in goldband snapper (Pristipomoides multidens) - Tonkin, Rachel Marie (Curtin University, 2012)
Introduction. Goldband snapper (Pristipomoides multidens) has an unusually long shelf life compared to many other fish species. Previous studies have indicated that the microflora present on the fish skin influences shelf life, however, no extensive studies have been performed. A comprehensive investigation into the shelf life of goldband snapper was undertaken in this study using microbiological, biochemical, sensory and physical analyses. Saddletail snapper (Lutjanus malabaricus) was used as a control species because it is genetically similar to goldband snapper, found in a similar geographic location but has a shorter shelf life. The implications of discovering the reasons for an increased shelf life are significant for the Australian fishing industry, in particular Western Australia, where transit times are extensive. It may be possible to use the knowledge gained by investigating goldband snapper to extend the shelf life of other tropical fish species.Methods. Bacterial viable counts were done from fish flesh using plate count agar (total plate count), iron agar (spoilage count) and long and hammer agar (psychrotrophic count). Various biochemical tests, MALDI-TOF analysis, fatty acid analysis and DNA sequencing were performed to identify each isolate to species level. Biochemical analyses of fish flesh were determined for TMA, employing colorimetry (picric acid method) TVB – N, using steam distillation (Kjeldahl method) and titration and hypoxanthine which employed high performance liquid chromatography. Sensory analyses were performed by trained sensory panellists who were enlisted to assess to the quality of saddletail snapper from different storage days (3, 10, 17, 24 and 31 days) using the QIM scheme. The Torry scheme, which assesses the flavour and odour of cooked fillets, was used to validate the results of the QIM assessment. The colour change seen with goldband and saddletail snapper throughout storage was measured using a Minolta spectrophotometer (CM-500i/CM-500C). The measured colours were expressed as CIE Lab coordinates which display as L*, a* and b*. The texture analysis method was based on measurements taken using a stable micro iiisystems (SMS) texture analyser (TA ·XT2i). The fish tested were compressed and the relaxation profile measured. Three points were measured along the lateral line of the fish and three samples were taken for every time point.Results. Overall, saddletail snapper had a higher number of specific spoilage organisms (SSOs) than goldband snapper. On average goldband snapper had a maximum of 1 x 108 CFU / g in comparison to saddletail snapper which peaked between 1 x 1011 and 1 x 1012 CFU / g. Variation within the microflora for both fish species was at its highest within the first 3 days of storage. The spoilage flora isolated from goldband snapper appeared to be more evenly distributed in comparison to saddletail snapper. This correlated with the lower numbers of SSOs present on goldband snapper (22.58%), compared to saddletail snapper (52.83%), immediately post harvest. The proportion of Gram positive organisms as a total of the microbial flora was higher on goldband snapper than saddletail snapper. The number of Gram positive organisms peaked immediately post harvest for goldband snapper and then followed a downward trend. Shewanella and Pseudomonas species were the significant SSOs for goldband and saddletial snapper. The Shewanella population constituted over 80% of the spoilage organisms present on saddletail snapper. Within 12 h the proportions were approximately even between Shewanella and Pseudomonas species. The Shewanella population constituted approximately 70% of the total spoilage organisms present on goldband snapper immediately post harvest. Within 12 h of storage this ratio had reversed with with Pseudomonas species now constituting 70% of the spoilage organisms present.TMA concentrations for goldband snapper remained lower at the beginning of storage compared to saddletail snapper, however, at day 17 of storage the levels of TMA for goldband snapper surpassed those of saddletail snapper. Both species remained below the TMA limit for human consumption, 10 – 15 mg / 100 g. The amounts of TVB-N were higher for goldband snapper for most of storage, however, at the end of storage the amount of TVB-N was much higher for saddletail snapper. Hypoxanthine levels for saddletail snapper remained between 20 and 40 mg / 100g. Goldband snapper had higher levels of hypoxanthine, starting at approximately 50 mg / 100g at the beginning of storage to approximately 100 mg / 100g by day 15 of storage.Saddletail snapper had a shelf life of only 24 days, using data collected from the QIM validation study. Textural analysis of saddletail snapper displayed a strong negative relationship with storage time, indicating that the fish became softer throughout storage. The texture of goldband snapper was soft and remained soft throughout storage, with the exception for a peak at day 17. The change in colour for both fish species was negligible and did not appear useful for determining spoilage, however, both goldband and saddletail snapper did increase in yellowness.ConclusionsBiochemical and sensory analyses demonstrated a difference existed between the spoilage of goldband and saddletail snapper, however, they did not explain why goldband snapper had a longer shelf life. Results from the microbiological analyses demonstrated that the microflora present on goldband snapper had an impact on its shelf life. The increased levels of Pseudomonas species at the beginning of storage appeared to limit the number of Shewanella species resulting in an extended shelf life. Investigation into the microflora of other tropical species to confirm these results needs to be undertaken. Testing for genetic differences between each of the Pseudomonas species should be also carried out and the spoilage potential needs to be quantified for each of the species isolated. The knowledge obtained from this project will contribute to a wider understanding of fish spoilage and allow treatments and other preventative measures to be developed to increase shelf life across a range of fish species caught in Australia.